2012
DOI: 10.1159/000341631
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Liquid and Solid Sucrose in Relation to Changes in Body Fatness over 6 Years among 8- to 10-Year-Old Children: The European Youth Heart Study

Abstract: Objective: To examine if intake of soft drinks is more closely associated with weight gain than other energy sources and if these associations are mediated through differences in energy intake or insulin level. Methods: Data derived from the Danish part of the European Youth Heart Study (n = 359). Height, weight, and waist circumference (WC) were measured in 1997-1998 and again in 2003-2004. Results: Intake of liquid sucrose was associated with changes in waist circumference (ΔWC) (β = 0.226, p = 0.07, R2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 37 publications
1
38
1
Order By: Relevance
“…Studies have reported that high energy intake is the main cause of excess weight 27 . Sugary beverages increase appetite more than solid foods given the low satiety and incomplete compensation of fluid calories, being an important contributor to higher fat deposition 14,28 . Since vitamin C reduces weight and visceral fat gain 3,4 , it may have helped to reduce weight gain in the study rats.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that high energy intake is the main cause of excess weight 27 . Sugary beverages increase appetite more than solid foods given the low satiety and incomplete compensation of fluid calories, being an important contributor to higher fat deposition 14,28 . Since vitamin C reduces weight and visceral fat gain 3,4 , it may have helped to reduce weight gain in the study rats.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,[24][25][26][27][28][29][30][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The methodological issues noted were mostly due to the complexity of assessing and measuring dietary intake. Because the majority of these studies were not designed to investigate the influence of SSB consumption on adiposity, the dietary tools used to collect data on SSB consumption were not optimal.…”
Section: Methodological Issues In Studies With a Neutral Quality Ratingmentioning
confidence: 99%
“…Among the 32 studies identified to answer our research question, 12 concluded that SSB consumption was associated with an increased risk of obesity in children or adolescents [19][20][21][22][23][24][25][26][27][28][29][30] and 13 found mixed results [31][32][33][34][35][36][37][38][39][40][41][42][43] ; for example, increase in girls but not in boys, among overweight children but not normal-weight children, or influence on body mass index (BMI) z score but not body fat percentage. Seven found no association 12,13,[44][45][46][47][48] between SSB consumption and risk of obesity.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Subjects were classified as either physically inactive (reported no or sometimes exercise) or physically active (reported regular exercise). The accelerometer measurements were used in a sensitivity analysis that found good agreement with the questionnaire method (24). A computer-based questionnaire was completed by parents to obtain demographic and socioeconomic data.…”
Section: Assessment Of Covariatesmentioning
confidence: 99%